Issue Information. Issue 4 (April 2016) - Unknown
Abstract : COVER PHOTOGRAPH: Right wholemount view of an E15.5 mouse heart after injection of red fluorescent wheat germ agglutinin into the left ventricle, showing the right coronary artery, including the coronary stem and branches. From Coronary stem development in wild‐type and Tbx1 null mouse hearts, Magali Theéveniau‐Ruissy, Joseé‐Maria Peérez‐Pomares, Pauline Parisot, Antonio Baldini, Lucile Miquerol and Robert G. Kelly, Developmental Dynamics 245:445–459. Read the full article at DOI:10.1002/dvdy.24380